(untitled) (Journal of School Administration Research and Development, 2020)
This study focused on educators’ beliefs about implementing a large-scale curriculum called Common Core State Standards (CCSS), or as they are identified in one state, College- and Career- Readiness Standards. Building–level educators in the state of West Virginia were surveyed using a modified Stages of Concern instrument that measures attitudes toward an innovation at a given point in its implementation (Hall et al, 1977). The research questions for the study were: (1) What is the comfort level of educators with new curriculum standards four years after adoption? and (2) What are the relationships among gender, grade level taught, the highest degree earned, and age on educators’ comfort level and concern toward a new curriculum set of standards? For research question one, the data showed that mathematics and English language arts teachers held a high awareness of the standards and were not overly concerned about the standards regarding time management. For research question two, simple regression results revealed significant relations between five of the seven stages of concern and some demographic variables: awareness with grade level taught and gender, informational with the highest degree obtained, personal with age, management with grade level taught, and collaboration with age. In general, educators who had more years of teaching, higher educational credentials, and were older were more likely to know where and how to obtain additional resources as well as get assistance, possibly as a result of their experiences and sociocultural capital gained over the years on the job. Administrators’ views were in alignment with teachers regarding their awareness of the standards and time management, and administrators were slightly more concerned with the consequences of the new standards and with teacher collaboration.